The effect of lamb carcase weight and GR depth on the production of value-added cuts – A short communication. (September 2017) - Fowler, Stephanie M.; Hoban, Jordan M.; van de Ven, Remy; Gardner, Graham; Pethick, David W.; Hopkins, David L.
Abstract: Times for the progressive breakdown of 95 lamb carcases were recorded to determine the impact of carcase weight and GR tissue depth on the time and therefore cost to produce value added retail cuts. Further analysis also assessed the potential to use these carcase traits as predictors of fabrication times. Regression modeling demonstrated there was a limited ability to predict the difference in time to fabricate mid value-added ( R 2 = 0.18) and extreme value-added ( R 2 = 0.12) cuts compared to traditional cuts, suggesting that other factors need to be considered. However, this study highlighted the significant increases in time required to fabricate more value-added cuts and to breakdown heavier carcases. Furthermore, this study demonstrated the changes to the saleable meat yield as the degree of fabrication increased, such that the average product prices increased (20.64/kg for mid value added and 28.72/kg for extreme value added) compared to traditional retail cuts (15/kg) to offset the increased labour of fabricating value-added cuts. Highlights: The cost of cut fabrication increases with more value-added cuts. The time taken to bone out carcases increased with the fabrication of value-added cuts. The time taken to bone out carcases increased with increasing carcase weight.